History of Roads and Evolution of Transportation: Effects on Regional Development in the Lower Wisconsin Riverway - Murphy, Mark; Thorpe, Chris; Bruun, Brad; Schaefer, Andy (My University, 2009)
Research on my topic has been qualitative and theory based. Its primary emphasis is to examine how past, present and future road building acts as a catalyst or reaction to population growth and economic development in the Lower Wisconsin Riverway. Also being explored is the increased reliance on the automobile from the early part of the twentieth century in contrast to after the Interstate Highway Act. The main goal of the research project will be to answer these questions and to develop a theory of our own as to how transportation infrastructure has affected the spatial layout of towns in the Riverway, its impact on growth and development, as well as looking into the future in predicting the effect new road construction will have on development. In our research we will be looking at historical documents, census data, maps, aerial photos, government documents, news publications, and conducting interviews.
Air Photos, maps.
Keywords: Lower Wisconsin Riverway; Regional Development; Transportation; Roads